Three Current Account Balances: A "Semi-Structuralist" Interpretation - Chinn, Menzie D.; Lee, Jaewoo (My University, 2005)
Three large current account imbalances the U.S. deficit and the two surpluses in Japan and in the euro area are subjected to a minimalist structural interpretation. This simple interpretation enables us to assess how much of each of the imbalances require a real exchange rate adjustment. According to the estimates, a large part of the U.S. current account deficit (nearly 2 percentage points of the 2004 deficit of 5 percent of GDP) will undergo an adjustment process that involves real depreciation in its exchange rate. For Japan, a little more than 1 percentage point of gross domestic product of the current account surplus is found to require an exchange rate movement (real appreciation) as the surpluses adjust down. For the euro area, less than half a percentage point of its current account surplus is found to require an adjustment via real appreciation.